The Effect of Total Quality Management (TQM) on Operational Performance in Garment Companies in Sukabumi - Sabil; Utiarahman, Nurnaningsih; Ananto, Niel; Lumingkewas, Cherry Frame (Eastasouth Institute, 2023)
TQM has emerged as an important management principle for improving operational performance in several sectors. The purpose of this research is to see how the influence of the TQM method on the operational performance of a clothing company in Sukabumi, Indonesia. Employee surveys were used to gather information, and multiple regression analysis was used to examine the relationship between TQM procedures and operational performance. Findings indicate that all elements of operational performance, including productivity, quality, cost, delivery, and flexibility, improve significantly through employee empowerment, continuous quality improvement, and fact-based management. The findings of this study have important implications for garment companies in Sukabumi and other similar industries in Indonesia.